1974
DOI: 10.1111/j.1469-8749.1974.tb03368.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Neurovestibular Responses in Infants

Abstract: SUMMARY A total of 121 babies were tested for the appearance of vestibular responses (nystagmus) within 10 and 75 days of birth. The babies were divided into two groups according to gestational age: full‐term (38 to 42 weeks gestation) and pre‐term (34 to 37 weeks gestation). These two groups were sub‐divided according to birthweight into small for gestational age (sga), appropriate for gestational age (aga) and large for gestational age (lga). Vestibular responses were elicited by per‐rotatory stimulation (us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is the author's experience that positional testing and bithermal caloric irrigation subtests of EOG have proven challenging when attempted with young children. A number of researchers have investigated maturation effects of nystagmic response during rotation (per-rotary) in young children (Eviatar et al, 1974;Eviatar et al, 1978). Although premature infants demonstrate weaker nystagmic response than full-term cohorts, the vestibular systems of premature babies maduración en niños pre-escolares hasta la edad adulta, y sugiere que los datos normativos de adultos pueden no ser apropiados cuando se interpretan resultados pediátricos.…”
Section: Sumariomentioning
confidence: 99%
“…It is the author's experience that positional testing and bithermal caloric irrigation subtests of EOG have proven challenging when attempted with young children. A number of researchers have investigated maturation effects of nystagmic response during rotation (per-rotary) in young children (Eviatar et al, 1974;Eviatar et al, 1978). Although premature infants demonstrate weaker nystagmic response than full-term cohorts, the vestibular systems of premature babies maduración en niños pre-escolares hasta la edad adulta, y sugiere que los datos normativos de adultos pueden no ser apropiados cuando se interpretan resultados pediátricos.…”
Section: Sumariomentioning
confidence: 99%
“…[56] The vestibuloocular response (VOR) is usually normal; however, Hoyt and Eviatar have shown that preterm infants with normal visual behavior may lack a fast-phase component to vestibuloocular testing. [9,61] The fast phase became presented by 1 month of age. If saccadic testing is abnormal, an MRI scan of the brain is indicated.…”
Section: Examinationmentioning
confidence: 99%
“…The VOR should be normal; however, a lack of the fast phase of the VOR has been reported in some normal preterm infants. [61] The assessment of saccades is crucial to help differentiate DVM from a global saccadic palsy or ocular motor apraxia. Brainstem saccadic dysfunction does not appear to be the cause of DVM as infants with DVM have been shown to have normal binocular full-field optokinetic nystagmus.…”
Section: Saccadic Eye Movementsmentioning
confidence: 99%